Factors Affecting Employability Skills of Beauty Students in Gerbang Kertosusila - Ningsih, Amina; Hariadi, Eko; Marniati, Marniati; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2021)
There is currently an imbalance between the skills mastered by vocational high school graduates with the skills needed in the labor market, especially employability skills, to maintain a job in various conditions and job requirements. This study aimed to examine the factors that affecting the employability skills of Beauty students namely career guidance, fieldwork practices, emotional intelligence, and self-efficacy. The respondents consisted of 254 students in Beauty Expertise Program at Gerbang Kertosusila. The instruments used in this study were questionnaire with a Likert scale and the statistical method using structural equation modeling (SEM). This study found no significant effect of career guidance, fieldwork practice, emotional intelligence, and self-efficacy on employability skills among Beauty students. The study also showed that career guidance and emotional intelligence have no significant effect on self-efficacy. However, fieldwork practice has a significant effect on the self-efficacy of Beauty students.